PERANCANGAN GEDUNG SEKOLAH TAHAN GEMPA DI CABANG MUHAMMADIYAH WEDI KLATEN - Widodo, Sri; Nugroho, M.S.Priyono; Setiawan, Budi (Universitas Muhammadiyah Surakarta, 2007)
Earthquake effect at 27 May 2006 have destroyed buildings ofMuhammadiyah effort in Wedi Klaten. The damages of buildings are cover:( a) TK ABA I and II have damages of roof and wall; ( b) TK Islamterpadu, children play group have total damage; ( c) SD Islam terpaduhave light damage. The damages of shool building have pursued theprocess of education at the school. In order to aim recovery the damagesschool, activity of this devotion to society is to give design of schoolbuilding which earthquake resitance, cheap, quickly construction andcan be developed. School building designed to one class unit, so that ifneeded some classes remain to combine it, and this combining isaccomodated with area and shape of land available. Designing by usingsystem of earthquake resistance. The concepts are as light as possibleand the and the building framework which consist of column, ring beamand sloof beam are made interaction so that forming room constructionthat having bigger moment of inertia. The activity of devotion to societyhave produced design of one class unit with size 6m x 8 m with buildingframework consist of reinforced concrete, wall from wood and roof madefrom waving zinc. One class unit is estimated require Rp.13,796,213.ofconstruction cost with duration of constructon is one month.